Efektifitas Metode Gallery Walk Pada Kelas Ibu Hamil Terhadap Pengetahuan Ibu Hamil di Wilayah Pare - Astri Yunita; Junianto Fitriyadi; Liya Ni'matul Maula; Dily Ekasari (Jenggala : Jurnal Riset Pengembangan dan Pelayanan Kesehatan, 2023)
Maternal and child health in Indonesia is an important issue in the health sector because of the high maternal and infant mortality rates. A critical indicator of women's health status is measured by the high maternal mortality rate. The gallery walk method is effective enough to improve the learning achievement index. The research design used quasy experiment with pre test post test. The independent variable of the study is the gallery walk learning method about the danger signs of pregnancy and the dependent variable is the knowledge of pregnant women about the danger signs of pregnancy. The study population was pregnant women aged 20-32 weeks of pregnancy totaling 31 pregnant women. The sample taken was all pregnant women aged 20-32 weeks of pregnancy totaling 31 pregnant women. The sampling technique in this study used total sampling. The research instrument used a questionnaire of the mother's knowledge level about pregnancy danger signs. Data analysis using Wilcoxon t-test. The results showed that there was a significant difference in the group before the intervention and after the intervention of the gallery walk learning method about the danger signs of pregnancy, with a p value = 0.000. The conclusion of the study is that health education using the gallery walk learning method is effective on the knowledge of pregnant women about the danger signs of pregnancy in the class of pregnant women.